FORMATION OF THE CREATIVE PERSONALITY OF THE FUTURE TEACHER IN THE CONTEXT OF THE MODERN EDUCATIONAL PROCESS HIGHER EDUCATIONAL INSTITUTION - Zaredinova Е. Р. (Pedagogy of Higher and Secondary Education, 2022)
In the article the necessity of forming of creative personality of future teacher is grounded in accordance with realities and requirements of modern society. On the basis of analysis of psychological and pedagogical literature an author the pedagogical terms of the effective forming of creative personality of future teacher are determined in the process of teaching in higher educational establishment.